The Problems encountered by students during Mathematics online learning viewed from Constructivism: a study of students' perspectives - Roslani; Ishaq Nuriadin (Universitas Muhammadiyah Prof. DR. HAMKA, 2022)
Constructivism learning theory is very relevant to be applied in Indonesia because it has advantages that can be used as an innovative learning method. However, the constructivism learning model is still rarely applied, especially in mathematics learning so that the learning objectives are not achieved properly. This research was conducted to obtain comprehensive information on how constructivism theory is used in online mathematics learning and the obstacles faced. This can be useful to find out good new adaptations in implementing online mathematics learning in the future. In addition, it can be useful as an evaluation material for the application of constructivism theory in online mathematics learning in the future. This research uses descriptive analysis method with literature study technique. The constructivism theory referred to in this study is a constructivist learning theory that has been explored in the application of online mathematics learning into four parts, namely: a learner-centered learning environment, a knowledge-centered learning environment, an assessment-centered learning environment, and an assessment-centered learning environment. community-centred learning. Â Teori pembelajaran konstruktivisme sangat relevan untuk diterapkan di Indonesia karena memiliki kelebihan yang dapat dijadikan metode pembelajaran yang inovatif. Namun model pembelajaran konstruktivisme masih jarang diterapkan khususnya pada pembelajaran matematika sehingga tujuan pembelajaran tidak tercapai dengan baik. Penelitian ini dilakukan untuk memperoleh informasi yang komprehensif tentang bagaimana teori konstruktivisme digunakan dalam pembelajaran matematika online dan kendala yang dihadapi. Hal ini dapat bermanfaat untuk mengetahui adaptasi baru yang baik dalam pelaksanaan pembelajaran matematika online di masa depan. Selain itu dapat bermanfaat sebagai bahan evaluasi penerapan teori konstruktivisme dalam pembelajaran matematika online di masa yang akan datang. Penelitian ini menggunakan metode deskriptif analisis dengan teknik studi literatur. Teori konstruktivisme yang dimaksud dalam penelitian ini merupakan teori pembelajaran konstruktivis yang dieksplorasi dalam penerapan pembelajaran matematika online menjadi empat bagian, yaitu: lingkungan belajar yang berpusat pada peserta didik, lingkungan belajar yang berpusat pada pengetahuan, lingkungan belajar yang berpusat pada penilaian. , dan lingkungan belajar yang berpusat pada penilaian. pembelajaran yang berpusat pada komunitas.